Preliminary findings on psychometric properties of the adolescent story stem profile - Zhang, Yinghao; Hillman, Saul; Pereira, Mariana; Anderson, Katharine; Cross, Richard M. (Frontiers in Psychology, 2025)
IntroductionThe Adolescent Story Stem Assessment Profile (ASSP) is a newly developed narrative measure aimed at assessing the psychological wellbeing of adolescents. This study investigates the psychometric properties of the ASSP within the British population, with the goal of elucidating its unique strengths and limitations.MethodsWe conducted an exploratory factor analysis on the responses of a community sample of adolescents in the UK (N = 182) to identify the underlying factors that reflect adolescents’ internal representations as measured by the ASSP. Following this, we performed a series of analyses on the responses from both the community sample and a high-risk sample of adolescents in care (N = 67) to investigate the psychometric properties of the ASSP.ResultsWe demonstrated satisfactory internal consistency, construct reliability, and discriminant validity among adolescents with varying levels of risk factors. The findings suggest that the ASSP is a promising tool for measuring mental health in adolescents, providing an economical and practically accessible method for both preventative and clinical applications.DiscussionOur results yield critical insights into the complex nature of adolescents’ psychological development, highlighting the necessity for tailored measures and interventions that address the diverse psychological needs of this population. Overall, this study represents a significant initial step toward establishing the ASSP as a valuable resource in both research and clinical practice, with implications for future studies aimed at enhancing our understanding of attachment to carers, peer relations, mentalization and affect competences in adolescence. The insights gained from this research underscore the importance of developing assessment tools that are sensitive to the unique psychological experiences of adolescents, ultimately contributing to more effective interventions and support strategies.